Juridical Analysis of Certain Time Work Agreements to Realize Legal Protection Measures for Workers (Research Study at PT. Delta Bridge Foods in Batam City) - Pangaribuan, Rospita; Respationo, Soerya; Anatami, Darwis (MultiTech Publisher, 2024)
Based on Law of the Republic of Indonesia Number 6 of 2023 concerning the Stipulation of Government Regulations instead of Law Number 2 of 2022 concerning Job Creation into Law, in Chapter IV Employment Part Two Article 56 which states as follows: paragraph (1) Work agreements are made for a certain time or for an indefinite time. The problem in this research is how the legal arrangements regarding fixed-term work agreements are to realize legal protection efforts for workers (Research study at PT. This research aims to find out the legal regulations regarding fixed-term work agreements, to realize legal protection efforts for workers (Research study at PT. Delta Bridge Foods in Batam City), to find out the implementation of the law regarding Specific Time Work Agreements (PKWT) to Realize Legal Protection Efforts (Research Study at PT. Delta Bridge Foods in Batam City), to find out what factors are obstacles /obstacles and solutions in certain time work agreements to realize legal protection efforts for workers (research study at PT. Delta Bridge Foods in Batam City). Research at PT. Delta Bridge Foods in Batam City) is regulated and established but in its implementation, there are still obstacles in the field.